A management system in the course formative research methodology of scientific research in race Management Systems engineering in Computerized (ISAC) of the Faculty of Administrative Sciences, University of Guayaquil - Viteri Briones, Telmo (Revista Universidad de Guayaquil, 2011)
The study describes a management system in the subject Formative Research Methodology of Scientific Research in Engineering in Computerized Management Systems (ISAC), Faculty of Administrative Sciences at the University of Guayaquil, pedagogical and educational experiment, which will begin with a general system for the University: reality training includes academic / research; Constitutional considerations and regulations of the State Constitution of Ecuador, the Higher Education Act, the Regulations of the National Academic System of Higher Education; the Science and Technology Policy 2007 - 2010 established by the Ministry of Higher Education, Science, Technology and Innovation (SENESCYT), The Institutional Development Strategic Plan, The Plan of the Directorate of Research and Academic Projects; currents of scientific / technical / research / education / teaching of Latin America and the World today the aim of creating a research team training (Seed Research) directing learning from the approach to problems (ABP); action research / participatory (IAP); The German Seminar, theoretical essays, research symposia, learning through discovery, participation in national / international research; in short, anything that involves the construction of teams that produce knowledge from information to solve the problems of their objects of study, But with a scientific and technological social processes, complex and interdisciplinary
Keywords: formative research; research incubators; management system